ISGylation and E3 ubiquitin ligases: an Atlantic salmon genetic perspective - Grimholt, Unni; Sindre, Hilde; Sundaram, Arvind Y. M. (Frontiers in Immunology, 2025)
IntroductionIn mammals, the ubiquitin–proteasomal pathway plays a key role in the host antiviral response by targeting viral genes for degradation. Here, E1-activating enzymes, E2-conjugating enzymes, and E3 ligases attach the ubiquitin chain to molecules to be functionally modified or destined for degradation. One specialized version of this pathway is performed by ISG15, a ubiquitin-like protein modifier that works through a process called ISGylation. In mammals, ISGylation involves specialized E1–E3 molecules and specialized mammalian ISG15 “deubiquitinases” also exist. Targeting host and viral proteins, ISG15 can inhibit the release of viral particles or hinder viral replication, thereby exerting strong antiviral effects. In Atlantic salmon, endothelial cells from the heart is a main target for infectious salmon anemia virus (ISAV). ResultsHere, we established a new cell line from Atlantic salmon heart tissue denoted ASH2-2, which has endothelial-like characteristics and is permissive for infection with ISAV and other salmonid viruses. We used this cell line as a model to compare the effect of recombinant interferon gamma (rIFNg) and ISAV on genes potentially involved in the ubiquitin–proteasome pathway. ASH2–2 cells have a response profile matching endothelial cells and respond quickly to ISAV infection with upregulation of viral sensors such as DHX58, MDA5, and MX transcripts. Two ISG15 genes are strongly upregulated 48 h post-infection (p.i.) while other ubiquitin genes were unaffected. Related to the mammalian E3 ligases known to be ISGylated, phylogenetic analysis identified two additional teleost-specific HERC8 and HERC9 clusters in addition to the clade previously defined as HERC7. Duplicate genes for Atlantic salmon HERC7 and HERC9 are both more upregulated by virus and rIFNg at 24 h p.i. as opposed to HERC8 genes. Early regulation of the ISGylation process is also indicated by a strong upregulation of one USP18 duplicate already at 4 h p.i.ConclusionIn conclusion, we expand the list of teleost genes potentially involved in the ubiquitin–proteasome pathway in cells from a main target organ. Our results highlight the need for functional studies to clarify the roles of these candidates.